Alterations in histamine metabolism of rat gastric mucosa following vagotomy - Lundell, L. (1974)
1. In female rats subjected to truncal vagotomy with pyloroplasty, pyloroplasty alone or sham operation, the behaviour of gastric mucosal histamine was investigated combining in vivo and in vitro methods. 2. Following truncal vagotomy with pyloroplasty mucosal histamine formation, determined in vitro, increased about fivefold and histamine content was significantly elevated. The heightened histamine formation was reflected in increased excretion of histamine in the urine. 3. On pentagastrin infusion, mucosal histamine formation increased about twofold following vagotomy with pyloroplasty and sevenfold in the sham-operated controls. Histamine content concomitantly fell in both groups to about the same level. These alterations were paralleled by increased excretion of histamine in the urine. 4. Kinetic studies in which [(14)C]histidine was injected and the resulting urinary [(14)C]histamine determined, indicated that during the first hour of pentagastrin infusion newly formed histamine was more slowly mobilized following vagotomy with pyloroplasty than in the controls. 5. In rats subjected to a pyloroplasty alone, the increase in urinary histamine on pentagastrin infusion was significantly larger than in the sham-operated controls. Kinetic studies indicated that this was due to a larger mobilization of preformed histamine. 6. The changes in mucosal histamine metabolism are discussed in relation to the pattern of acid secretion following the actual surgical procedures.